Mechanical property degradation of X80 pipeline steel due to microbiologically influenced corrosion caused by Desulfovibrio vulgaris - Li, Zhong; Yang, Jike; Guo, Huihua; Kumseranee, Sith; Punpruk, Suchada; Mohamed, Magdy E.; Saleh, Mazen A.; Gu, Tingyue (Frontiers in Bioengineering and Biotechnology, 2022)
Apart from pinhole leaks, MIC (microbiologically influenced corrosion) can also cause catastrophic failures such as pipe ruptures and support beam collapses due to mechanical property degradation or stress corrosion cracking. In this work, X80 pipeline steel dogbone coupons and square coupons were immersed in 150 mL broths containing Desulfovibrio vulgaris, a common corrosive sulfate reducing bacterium (SRB), for up to 14 days. The headspace volumes in the anaerobic bottles were increased from 150 mL to 200 mL and 300 mL to increase MIC severity. After 14 days of SRB incubation in ATCC 1249 culture medium with X80 coupons at 37 oC, the sessile cell counts were 6.5×107 cells cm−2 for 150 mL, 2.3×108 cells cm−2 for 200 mL and 1.4×109 cells cm−2 for 300 mL headspace volumes, respectively owing to reduced H2S cytotoxicity in the broth with a larger headspace because it allowed more biogenic H2S to escape from the broth. Weight losses were 1.7 mg cm−2, 1.9 mg cm−2 and 2.3 mg cm−2 for 150 mL, 200 mL and 300 mL headspace volumes, respectively. The corresponding pit depths were 2.6 μm, 4.2 μm and 6.2 μm for 150 mL, 200 mL and 300 mL headspace volumes, respectively. Electrochemical impedance spectroscopy (EIS), linear polarization resistance (LPR) and potentiodynamic polarization results corroborated the increasing weight loss and pitting data trends as a result of increased headspace. Tensile testing of dogbone coupons after the 14-day SRB immersion test indicated that more severe MIC pitting led to a higher ultimate strain loss by up to 23% (300 mL headspace) compared to the abiotic control, while the ultimate strength losses for all headspace volumes were quite small (3% and lower).